EDM machinability and parametric optimisation of 2014Al/Al2O3 composite by RSM. (2018) - Khajuria, Akhil; Bedi, Raman; Singh, Balbir; Akhtar, Modassir
The present work investigates the machinability and influence of process parameters on the machining characteristics in EDM of AA2014/Al2 O3 composite. The composite was fabricated through stir casting technique. Process parameters considered are current, voltage, pulse on time and wt.% reinforcement for the purpose of optimisation. Machining characteristics viz. MRR, TWR and SR are investigated. Experiments were designed by adopting rotatable centred composite design based on RSM. The machined surface is further analysed by SEM-EDS. Results revealed that MRR, TWR and SR increase with an increase in the current and pulse on time. However, less TWR and good surface finish are obtained at the lower setting of current, pulse on time and optimum setting of voltage and wt.% reinforcement. Performance measures recorded experimentally at optimum values of process parameters, i.e., 12 A current, 60 V voltage, 60 µm pulse on time and 5 wt.% Al2 O3 /AA2014 reinforcement are 0.1501 g/min MRR, 0.0032 g/min TWR and 9.367 µm SR.